THE INFLUENCE OF DEFERRED TAX BURDEN, LEVERAGE, AND TAX PLANNING ON EARNINGS MANAGEMENT IN CONSUMER GOODS SECTOR COMPANIES FOR THE PERIOD 2018-2022 - Merry; Cheong Shiau Wie; Dwita Sakuntala; Tina Novianti Sitanggang (Mount Hope Economic Global Journal, 2024)
The purpose of this research is to examine the impact of deferred tax burden, leverage, and tax planning on earnings management in consumer goods sector companies during the period of 2018-2022. The research population consists of 50 consumer goods sector companies listed on the Indonesia Stock Exchange, with a sample size of 19 companies obtained over a five-year period. The sampling method used is purposive sampling. Data analysis is conducted using multiple linear regression. The results of the F-test indicate that deferred tax burden, leverage, and tax planning simultaneously influence earnings management. Partially, only two variables have an effect: the deferred tax burden has a positive and significant effect on earnings management, and tax planning has a negative and significant effect on earnings management. The Adjusted R² value of 0.102 indicates that only 10.2% of the variation in earnings management can be explained by deferred tax burden, leverage, and tax planning, while the remaining 89.9% is explained by other variables not examined in this study.